Fractional-Order Asymptotical Phase Shifter With Flat Magnitude Response - Šotner, Roman; Langhammer, Lukáš; Jeřábek, Jan; Dostál, Tomáš (IEEE, 2019)
This work deals with design of fractional-order asymptotical phase shifter having constant magnitude response within almost three decades (100 Hz – 100 kHz) and frequency dependent phase difference going from 0 to 45 degrees. PSpice simulations employing macromodels of off-the-shelf active parts brought the results suitable for brief analysis of the complete solution of our phase shifter in both frequency and time domain. Magnitude flatness with only ±0.3 dB variation and maximal phase error in the middle of operational bandwidth 3.7 degrees prove very good performance of designed circuit.

This work deals with design of fractional-order asymptotical phase shifter having constant magnitude response within almost three decades (100 Hz – 100 kHz) and frequency dependent phase difference going from 0 to 45 degrees. PSpice simulations employing macromodels of off-the-shelf active parts brought the results suitable for brief analysis of the complete solution of our phase shifter in both frequency and time domain. Magnitude flatness with only ±0.3 dB variation and maximal phase error in the middle of operational bandwidth 3.7 degrees prove very good performance of designed circuit.
Fractional-Order Asymptotical Phase Shifter With Flat Magnitude Response
Keywords: All-pass filter; constant phase element; fractional-order; phase shifter; variable gain amplifier; All-pass filter; constant phase element; fractional-order; phase shifter; variable gain amplifier